Spectral index asymmetries in double radio sources and the unified model - Blundell, K (1996)
A model is presented which reconciles the conflicting implications of the Garrington-Laing effect and the Liu-Pooley effect, which had caused difficulties for the projection model and hence for unified schemes. I also show that DPM asymmetries are significantly larger for quasars than for radio galaxies, adding further weight to the suggestion that quasars are closer to the line of sight. Copyright ©1996 Elsevier Science Ltd.